2005
DOI: 10.1038/modpathol.3800282
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of heparanase expression with tumor invasion and lymphatic metastasis in gastric carcinoma

Abstract: Tumor invasion and metastasis are the most common causes of death in gastric carcinoma. Human heparanase influences tumor invasiveness and angiogenesis. Analysis of its expression in gastric carcinoma has been hindered by our inability to procure pure cancer cells from heterogeneous tissue. In the present study, we analyzed heparanase expression in human primary and metastatic gastric carcinoma cells as well as in paired normal gastric epithelial cells by laser capture microdissection coupled with reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…It is widely accepted that tumor metastasis begins with the degradation of the ECM and breakdown of the basement membrane (13). Our previous studies demonstrated an increased expression of HPSE in GC tissues and identified that HPSE facilitates invasion and metastasis of GC cells (13,14). However, the underlying molecular mechanism of the upregulation of HPSE in GC tissues remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that tumor metastasis begins with the degradation of the ECM and breakdown of the basement membrane (13). Our previous studies demonstrated an increased expression of HPSE in GC tissues and identified that HPSE facilitates invasion and metastasis of GC cells (13,14). However, the underlying molecular mechanism of the upregulation of HPSE in GC tissues remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In highly metastatic B16-BL6 mouse melanoma cells, transfection of mouse HPA-specific siRNA resulted in a decrease in the invasiveness and metastasis of tumor cells [14] . Previous studies indicated that the expression of HPA was frequently obser ved in advanced gastric cancers, and the frequency was significantly correlated with histopathological parameters reflecting invasive and metastatic potentials and prognosis of gastric cancers [6,7] . Our studies also demonstrated the overexpression of HPA protein in advanced gastric cancer (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Heparanase (HPA), a mammalian endo-beta-D-glucuronidase, is capable of degrading the heparan sulfate proteoglycans (HSPGs) in the ECM and BM, and is proposed to have a promoting role in cancer invasion, angiogenesis and metastasis [5] . In advanced gastric cancer, expression of HPA was frequently observed and correlated with histopathological parameters reflecting the invasiveness, metastatic potential and prognosis of gastric cancers [6,7] . Thus HPA may represent an important target for treatment of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The RhoA and RhoC proteins comprise an important s u b s e t o f t h e R h o G T Pa s e f a m i l y t h a t h a s b een implicated in invasive gastric carcinomas, and is related to the PI3K/Akt signal pathway. To dissect the specific contributions of RhoA and RhoC in the behavior of invasive gastric carcinoma cells, we used RhoA and RhoC gene interference to inhibit proliferation and invasion of SGC7901 cells of gastric carcinoma [7,8] . We have used small interfering RNA (siRNA) approaches to interfere www.wjgnet.com the expression of the RhoA and RhoC isoforms in the SGC7901 cells.…”
Section: Introductionmentioning
confidence: 99%